Metabolic Effects of Mulberry Leaves: Exploring Potential Benefits in Type 2 Diabetes and Hyperuricemia. (5th December 2013) - Hunyadi, A.; Liktor-Busa, E.; Márki, Á.; Martins, A.; Jedlinszki, N.; Hsieh, T. J.; Báthori, M.; Hohmann, J.; Zupkó, I.
Abstract : The leaves of Morus alba L. have a long history in Traditional Chinese Medicine and also became valued by the ethnopharmacology of many other cultures. The worldwide known antidiabetic use of the drug has been suggested to arise from a complex combination effect of various constituents. Moreover, the drug is also a potential antihyperuricemic agent. Considering that type 2 diabetes and hyperuricemia are vice-versa in each other's important risk factors, the use of mulberry originated phytotherapeutics might provide an excellent option for the prevention and/or treatment of both conditions. Here we report a series of relevant in vitro and in vivo studies on the bioactivity of an extract of mulberry leaves and its fractions obtained by a stepwise gradient on silica gel. In vivo antihyperglycemic and antihyperuricemic activity, plasma antioxidant status, as well as in vitro glucose consumption by adipocytes in the presence or absence of insulin, xanthine oxidase inhibition, free radical scavenging activity, and inhibition of lipid peroxidation were tested. Known bioactive constituents of M. alba (chlorogenic acid, rutin, isoquercitrin, and loliolide) were identified and quantified from the HPLC-DAD fingerprint chromatograms. Iminosugar contents were investigated by MS/MS, 1-deoxynojirimycin was quantified, and amounts of 2- O -alpha-D-galactopyranosyl-1-deoxynojirimicin and fagomine were additionally estimated.